The effect of dynamic mathematics software on mathematical problem solving ability. Issue 1 (May 2021) - Lan, X; Zhou, Y; Wijaya, T T; Wu, X; Purnama, A
Abstract: Mathematics is one of the fields of science that is very important for humans because all science is related to mathematics. One of the skills that should be learned and developed in mathematics is mathematical problem-solving ability. Problem-solving ability is highly needed because humans are always used in everyday life, both in education and daily life. In fact, students' problem-solving abilities are lacking. This is because mathematical problems created by teachers are not based on indicators of problem-solving ability. Triangle is the important material of two-dimensional figures in elementary school. Teachers need to explain the basic concept of a triangle so that students can master a more difficult concept of a triangle. Dynamic mathematics software can help students grasp the concept of triangles. This study used a quantitative method. This study is a comparison between classes using Hawgent and using conventional methods. The subjects in this study were 72 seventh-grade students in Cianjur, Indonesia. Data were collected based on the results of the pre-test and post-test problem-solving ability. Based on the study results, the class using Hawgent is more good than the class that using the traditional method. Hawgent has been proven to help students understand triangle material.